Practice change in community health centers: A qualitative study of leadership attributes - Tektiridis, Jennifer H.; Heredia, Natalia I.; Morgan, Robert O.; Mikhail, Osama I.; Risendal, Betsy C.; Kegler, Michelle C.; Fernandez, Maria E. (Frontiers in Health Services, 2022)
Introduction This paper explores leadership attributes important for practice change in community health centers (CHCs) and assesses attributes' fit with the Full-Range Leadership Theory (FRLT). Methods We conducted four focus groups and 15 in-depth interviews with 48 CHC leaders from several U.S. states using a modified appreciative inquiry approach. Thematic analysis was used to review transcripts for leadership concepts and code with a priori FRLT-derived and inductive codes. Results CHC leaders most often noted attributes associated with transformational leadership as essential for practice change. Important attributes included emphasizing a collective sense of mission and a compelling, achievable vision; expressing enthusiasm about what needs to be done; and appealing to employees' analytical reasoning and challenging others to think creatively to problem solve. Few expressions of leadership fit with the transactional typology, though some did mention active vigilance to ensure standards are met, clarifying role and task requirements, and rewarding followers. Passive-avoidant attributes were rarely mentioned. Conclusions Our results enhance understanding of leadership attributes supportive of successful practice change in CHCs.